Between Aquinas and Eymerich: The Roman Inquisition's Use of Dominican Thought in the Censorship of Alchemy. (3rd July 2018) - Tarrant, Neil
Abstract : In the latter half of the sixteenth century the Roman Inquisition developed criteria to prosecute a series of operative arts, including various forms of divination and magic. Its officials had little interest in alchemy. During that period the Roman Inquisition tried few people for practising alchemy, and it was rarely discussed in official documents. Justifications for prosecuting alchemists did exist, however. In his influential handbook, Directorium inquisitorum, the fourteenth-century inquisitor Nicholas Eymerich had developed a clear rationale for the investigation and prosecution of alchemists as heretics. His position was endorsed in the 1570s by Francisco Peña in his commentary on Eymerich's handbook. In this article I explore the reasons why alchemy held this ambiguous status. I argue that members of the Dominican Order developed two traditions of thinking about alchemy from Aquinas's thought. The first, and closest to Aquinas's own belief, held that alchemy was a natural art that posed no danger to the Christian faith. The second, developed by Eymerich from a selective reading of Aquinas's writings, indicated specific circumstances in which alchemists could be investigated. The Roman Inquisition's response to alchemy vacillated between the positions advocated by Aquinas and Eymerich.